Importance of Improving Resilience in Teaching-Learning Process of Students with Disabilities - MacÃƒÂas, Eleticia Isabel Pinargote; CedeÃƒÂ±o, HernÃƒÂ¡n AndrÃƒÂ©s CedeÃƒÂ±o; ChÃƒÂ¡vez, Gabriela Monserrate Romero (International Research Journal of Management, IT & Social Sciences, 2018)
The objective of the work focuses on determining the importance of resilience in the teaching-learning process of students with disabilities at the Technical University of ManabÃ, for this purpose an exploration is carried out to verify the criterion on this concept students group. The work deals with contemporary contextual aspects that may favor a psychosocial approach to resilience. The article is based on qualitative research based on the qualitative interpretative-hermeneutic paradigm. The theoretical referents were consigned from the bibliographic review, with the purpose of confronting them with the empirical phase that allowed to unravel the individual representations of the interviewees about the resilience. The results of the research show that resilience is widely known, although an important bias is maintained in its representation related to a more individual than the social view, which could limit its influence as a pedagogical factor.